Analisis Makna Gramatikal Jouken Hyougen To dan Tara dalam Drama Okuribito - Siswoyo Siswoyo (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2018)
This thesis discusses the substitutions of to and tara conjunction terms of grammatical meaning occour in Okuribito drama. It aims to analyze the substitution of to and tara. The data analysis was conducted by using distributional qualitative method with syntactic and semantic design based on Suzuki Shinoruâ€™s theory. The results of reveal that to and tara conjunctions are mutually substitutable when they show the following meaning: general situation, habitual, hope, thought, and constancy. However, they are not mutually substitutable when they are used to show: assumption, permission, wish, action, intention and advice.Â Keywords: Conditional Sentence, To Conjunction, Tara Conjunction, Substitution, Synonym.